2018
DOI: 10.1038/modpathol.2017.110
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary large cell neuroendocrine carcinoma with adenocarcinoma-like features: napsin A expression and genomic alterations

Abstract: Pulmonary large cell neuroendocrine carcinoma (LCNEC) is a highly aggressive malignancy, which was recently found to comprise three major genomic subsets: small cell carcinoma-like, non-small cell carcinoma (predominantly adenocarcinoma)-like and carcinoid-like. To further characterize adenocarcinoma-like subset, here we analyzed the expression of exocrine marker napsin A, along with TTF-1, in a large series of LCNECs (n=112), and performed detailed clinicopathologic and genomic analysis of napsin A-positive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 37 publications
1
53
0
Order By: Relevance
“…In TTF1-positive nonsmall cell tumors, napsin A may play a role in classification of NE tumors, as it may be positive in a subset of large cell NE carcinomas (LCNECs), which are molecularly similar to adenocarcinoma, helping to separate them from high-grade NE tumors such as small cell carcinoma, which are typically napsin A-negative. 7,8 The use of surfactant protein A is discouraged, as its performance is inferior. 9,10 As a marker of squamous cell carcinoma, p63 was more frequently used in IHC analysis before introduction of the p40 antibody.…”
Section: Key Questionsmentioning
confidence: 99%
“…In TTF1-positive nonsmall cell tumors, napsin A may play a role in classification of NE tumors, as it may be positive in a subset of large cell NE carcinomas (LCNECs), which are molecularly similar to adenocarcinoma, helping to separate them from high-grade NE tumors such as small cell carcinoma, which are typically napsin A-negative. 7,8 The use of surfactant protein A is discouraged, as its performance is inferior. 9,10 As a marker of squamous cell carcinoma, p63 was more frequently used in IHC analysis before introduction of the p40 antibody.…”
Section: Key Questionsmentioning
confidence: 99%
“…In the differential diagnosis of LCNEC versus SCLC, staining of RB1 IHC is indicative of a non‐SCLC‐like tumour . Finally, napsin‐A is proposed as a marker to differentiate the TTF1‐positive molecular LCNEC‐NSCLC subtype from adenocarcinoma, as only few show focal staining for napsin‐A while all adenocarcinomas show (strong) staining for both markers …”
Section: Discussionmentioning
confidence: 99%
“…4 Finally, napsin-A is proposed as a marker to differentiate the TTF1-positive molecular LCNEC-NSCLC subtype from adenocarcinoma, as only few show focal staining for napsin-A while all adenocarcinomas show (strong) staining for both markers. 36 Our study was restricted by the limited number of paired biopsy-resection specimens evaluated by the panel of pathologists. Nevertheless, the described diagnostic issues in this study reflect the daily clinical practice closely.…”
Section: Discussionmentioning
confidence: 99%
“…8,14 Although napsin A expression is not seen in TCs, ACs, or SCC, it can be expressed in a subset of LCNEC at a lower level than adenocarcinoma; it was shown that these LCNECs harboured mutations typical of lung adenocarcinoma. 38 Of note, 5% to 10% of SCCs and LCNECs may lack expression of all 3 neuroendocrine markers. 34 The proliferation index is high (40% to 80%), and necrosis may be present.…”
Section: Cancer Cytopathology August 2018mentioning
confidence: 99%